Estimasi Underground Economy Tingkat Provinsi di Indonesia - P.M, Gusrah Kharisma; Khoirunurrofik, Khoirunurrofik (UI Scholars Hub, 2021)
This study try to measure the size of the provincial-level underground economy in Indonesia using a monetary approach. Measurements were made in the study period 2007 - 2017, using Ordinary Least Square regression, to estimate the currency demand due to underground economy activities at the regional level that are affected by regional tax burdens. Estimates in this study resulted in the amount of underground economy ranging from 3.8% - 11.6% of the GRDP with an average of 8% per province per year.